Corporate Criminal Liability in Indonesian Law Concerning Fund Transfer - M. N. B. Asyhar Assalmani (Publindo Akademika, 2021)
Fund transfers can now be done virtually. Innovations in fund transfers have not only positive but also negative impacts. Legal protection is needed so that there is legal certainty for the community in carrying out fund transfer activities. Law No. 3 of 2011 concerning Funds Transfer is a statutory regulation that was passed to provide such protection. This paper aims to describe the corporate criminal liability in Indonesian law concerning fund transfer. One arrangement that is different from the general provisions of the Criminal Code is related to the subject of criminal law. The Funds Transfer Law expands the subject of criminal law, namely not only humans but also corporations. Unfortunately, the expansion of the subject of criminal law in the Funds Transfer Law is not accompanied by the existence of a new type of crime. The absence of new crimes in the Funds Transfer Law can be used by corporations to not carry out court decisions.